Global business shunning hospitality jobs: a disguised power struggle?. (8th July 2019) - Vassou, Chrystalla; Christofi, Michael; Simillidou, Aspasia; Vrontis, Demetris
The hospitality industry has been portrayed as producing precarious workers by recruiting foreigners who are willing to work for lower salaries, under unregulated working conditions, and with limited opportunities for development and career progression. This situation has earned the industry a negative image among the host population, triggered by the belief that hospitality jobs are low-status and should be avoided. This study explored the mechanisms of this phenomenon in order to provide a more in-depth understanding of its emergence. Informed by intergroup conflict theory and in-depth interviews, this study shows that perceived threat lies at the heart of prejudice formation, which is the host population's mechanism to remove competition. Adding to this, the findings also show that long-term challenges entailed in hospitality employment cannot be understood unless structural issues are taken into account. The managerial and policy implications of these results are discussed.